Avaliação de estudos de judicialização de medicamentos: uma revisão sistemática - Lyra, Pollyanna Farias Castro Pereira de (2016)
Objective: We keek to identify the profile of studies on judicialization of medicines in the literature. Methods: A systematic review was conducted in four major databases, using descriptors such as "judicialization", "medicines", "right to health", combined in different ways. The inclusion criteria were used: studies published from January 1990 to March 2015, involving studies on judicialization only medicines and their influence on the service/ management of pharmaceutical services. The quality of the methodological research of the selected studies was assessed according to the STROBE recommendations. Results: Our survey included 25 articles to read in its entirety, by two evaluators. In the studies analyzed was detected the lack of methods, protocols or technical and scientific advice for evaluating the processes judicialization of medicines. The most requested therapeutic classes are associated with major prevalent diseases in the population. Antineoplastic drugs and immunomodulatory agents are among the most frequently ordered medicines. Most judges granted favorable decisions without considering the scientific technical criteria and most of the studies did not report spending on lawsuits. Most studies showed low adherence to criteria suggested by the STROBE. Conclusion: The study showed high heterogeneity, with lack of standardization in the process of analyzing the judicialization of medicines, making it difficult to compare the data and generalize the results. Protocols and practice documentation are needed to guide and standardize the work process of judicialization and measure the impact of interventions of the Scientific Support Units.